Nonlinear unmanned aerial vehicle formation control via composite Laplacian quadratics. Issue 2 (12th March 2020) - Jing, Peng; Chen, Fei
Abstract : This article studies a leader‐following formation control problem, in which the agent model is governed by continuous‐time nonlinear differential equations. We are interested in designing a distributed control algorithm which is capable of handling the strong nonlinearities induced by the unmanned aerial vehicle model. Our primary objective is to investigate the convergence of the corresponding closed‐loop system, and to understand how the nonlinear dynamics and the network topologies may impose intrinsic barriers on formation control. The results show that an exponential convergence is guaranteed under the proposed algorithm via the composite Laplacian quadratics function as long as the network topology has a directed spanning tree. Abstract : Composite Laplacian quadratics and linear differential inclusions with an application to formation control for unmanned aerial vehicles.